Enzymatic modification of paper fibres - Pala, H. (2002)
The enzymatic mode of action in paper fibre upgrading is still uncertain. In an attempt to clarify how enzymes modify pulp and paper properties, several parameters were analysed in the present work: (i) thermal analysis of the water–solid surface interactions; (ii) fibre cake permeability; (iii) particle size analysis. The results obtained suggest that enzymes modify the interfacial properties of fibres, increasing the water affinity, which in turn change the technical properties of pulp and paper, such as drainability and strength. The modification of paper and pulps following a treatment with cellulosebinding domains further supports this hypothesis.